A Comparative Study of Three-Dimensional Simulation in Nonsurgical Rhinoplasty With Hyaluronic Acid Fillers. Issue 2 (March 2021) - Chen, Chuhsin; He, Junjun; Xiong, Zhezhen; Xue, Ke; Liu, Kai
Abstract : Background: The use of 3-dimensional computer imaging has grown steadily over the past decade, especially with cosmetic facial surgery. The technological advance has influenced how we counsel patients, perform procedures, and assess outcomes. The purpose of this study was to analyze the feasibility of quantifying simulated versus actual outcomes for nonsurgical rhinoplasty with hyaluronic acid. Methods: A retrospective review of 3-dimensional images (LifeViz Inc, France) for rhinoplasty patients was performed. Randomized preoperative, simulated, and actual images were rated by a blinded panel of physicians (1 = poor, 5 = excellent). In addition, a quantitative assessment of nasofrontal angle and nasolabial angle was conducted where paired and 2-sample t tests were performed ( P < 0.05 as significant). Results: Twenty-five patients were included in this comparison study. Fifty-six percent of preoperative images were rated as poor (mean, 1.7). The simulation received a mean score of 3.4 (good in 60% of cases), and 80% of actual cases were rated good to excellent (mean, 3.7). Mean nasofrontal angle decreased from 147.1 ± 1.2° preinjection to 143.3 ± 1.6° posttreatment, a mean change of 3.8 ± 2.0°. The mean nasolabial angle decreased from 125.5 ± 1.6° pretreatment to 117.5 ± 1.5° posttreatment. Average volume of actual dosage was 1.74 ± 0.18 mL. Conclusion: Three-dimensional simulation for patients undergoing nonsurgical rhinoplasty is helpful for surgical planning and patient communications. It provides a mechanism for critical self-evaluation and helps set patients with realistic expectations about rhinoplasty.